2010
DOI: 10.1073/pnas.1001222107
|View full text |Cite
|
Sign up to set email alerts
|

Rice yields in tropical/subtropical Asia exhibit large but opposing sensitivities to minimum and maximum temperatures

Abstract: Data from farmer-managed fields have not been used previously to disentangle the impacts of daily minimum and maximum temperatures and solar radiation on rice yields in tropical/subtropical Asia. We used a multiple regression model to analyze data from 227 intensively managed irrigated rice farms in six important riceproducing countries. The farm-level detail, observed over multiple growing seasons, enabled us to construct farm-specific weather variables, control for unobserved factors that either were unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
376
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(403 citation statements)
references
References 30 publications
24
376
0
3
Order By: Relevance
“…Wu et al (2015) found out rice production to be sensitive to temperature, precipitation and sunlight in Taiwan. The impacts of temperature and solar radiation on rice yield are poorly understood despite many decades of agronomic research on rice crop (Welch et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al (2015) found out rice production to be sensitive to temperature, precipitation and sunlight in Taiwan. The impacts of temperature and solar radiation on rice yield are poorly understood despite many decades of agronomic research on rice crop (Welch et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The respiration process appears to make rice plants particularly sensitive to nighttime temperature (Yin et al 1996). Several studies have highlighted nighttime temperatures as a driving factor of rice growth, where elevated minimum nighttime temperatures greatly reduce rice yields (Yin et al 1996;Peng et al 2004;Welch et al 2010). Using a laboratory experiment to artificially manipulate temperatures, Yin et al (1996) demonstrate that a one-degree increase in nighttime temperature has a large negative effect on rice yields whereas a one-degree increase in daytime temperature has a slightly positive effect.…”
Section: The Role Of Temperaturementioning
confidence: 99%
“…Exposure of crops to these extreme higher temperatures during sensitive stages of development reduces yield significantly. Rice is a major staple crop growing in irrigated systems in South Asia where the temperature exceeds critical threshold level (Nakagawa et al 2002) and its productivity is decreased by increasing seasonal temperature (Welch et al 2010). The sensitivity to heat stress varies with species and cultivars, the duration and intensity of heat stress, the phenological stage of the plants, and several other Electronic supplementary material The online version of this article (doi:10.1007/s12298-016-0350-6) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%